Politics of orality - Cooper, Craig R. 1960- (Mnemosyne, bibliotheca classica Batava. Supplementum,, 2007)
This volume represents the sixth in the series on Orality and Literacy in the Ancient Greek and Roman Worlds. The present work comprises a collection of essays that explore the tensions and controversies that arise as a society moves from an oral to literate culture. Part 1 deals with both Homeric and other forms of epic; part 2 explores different ways in which texts and writing were manipulated for political ends. Part 3 and 4 deals with the controversies surrounding the adoption of writing as the accepted mode of communication; whereas some segments of society began to privilege writing over oral communication, others continued to maintain that the latter was superior. Part 4 looks at the oral elements of Athenian Law.